Autobiografia e Ficção: análise do narrador em Extinção - Uma Derrocada, de Thomas Bernhard - Santos, José Lucas Zaffani dos [UNESP] (2015)
The present dissertation aims to analyze the book Extinction - a collapse, of the Austrian writer Thomas Bernhard, published in 1986. The novel, related by Franz-Josef Murau, presents as a narrative situation the wish of this character to write his autobiography, as soon as he returns from Wolfsegg - where he attended his relatives' funeral - to Rome, where he lives since he left his family. However, in the end, after being announced the narrator's death, the same text can be read as the embodiment of his autobiographical project. Thus, this analysis starts from the constitution of the narrator-protagonist to reflect about his intention in writing his account, which has as the theme to deal with his homeland, Wolfsegg, in Austria. This research also aims to show the role of writing as a way of elaborating the traumatic past lived by the narrator beside his family, in Wolfsegg. This place reigns in the narrator's speech as absolute and, being the thematic core of his writing, it will also be analyzed to delineate the person who tells his story. It's necessary to discuss how this narrator selects and sorts the events which he describes because the novel is dominated by his view - in first person. These events intend to enhance the image that the protagonist wants to create of himself. In this novel, narrator and space categories seem to be only one and the writing designed by Murau must present the extinction of both